Peningkatan Hasil Belajar Peserta Didik Dengan Penerapan Model Project Based Learning Menggunakan Media Visual Pada Materi Teks Berita Kelas VII SMP Negeri 61 Palembang - Titania, Debi; Rukiyah, Siti (Penerbit Yayasan Daarul Huda Kruengmane, 2024)
This research is a Classroom Action Research aimed at improving the learning outcomes of seventh-grade students in Class VII.1 at SMP Negeri 61 Palembang in the subject of Indonesian Language, specifically on the topic of news text, using the Project Based Learning (PjBL) model. The implementation follows a cycle of Planning, Action, Observation, Reflection, and Re-planning, which forms the basis for problem-solving strategies. Based on the research data collected, the pre-cycle learning showed an average score of 47.0, with 4 out of 31 students achieving a mastery level of 13%. This improved but did not yet meet the expected criteria in Cycle 1, where the average score was 56.0, and 11 out of 31 students reached a mastery level of 35%. Subsequently, in Cycle 2, the average score increased to 75.96, with 26 out of 31 students achieving a mastery level of 84%. The learning outcomes in Cycle 2 met the expected criteria, with an average score ? 65. Therefore, it can be concluded that the use of the Project Based Learning (PjBL) model led to an improvement in the learning outcomes of the seventh-grade students at SMP Negeri 61 Palembang in the subject of Indonesian Language, specifically in the topic of news text, when using visual media.